2016
DOI: 10.3201/eid2205.151835
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Septicemia Linked to Transmission of MRSA Clonal Complex 398 in Hospital and Nursing Home, Denmark

Abstract: We describe 2 fatal cases of methicillin-resistant Staphylococcus aureus (MRSA) clonal complex 398 septicemia in persons who had no contact with livestock. Whole-genome sequencing of the isolated MRSA strains strongly suggest that both were of animal origin and that the patients had been infected through 2 independent person-to-person transmission chains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 12 publications
1
20
0
Order By: Relevance
“…Pairwise SNP comparison showed that the isolates were identical to each other ( Figure 2 and Supplementary Figure 1), which supports transmission between these patients or acquisition from a common hospital source. In addition, 2 patients with community-onset LA-MRSA CC398 BSI, a 63-year-old man receiving outpatient dialysis (case E) and a 74-year-old male nursing home resident (case I), were previously reported to be part of 2 distinct healthcare outbreaks [ 14 ]. All 5 isolates from cases E, P, and Q were closely related to Danish pig isolates (range, 14–16 SNPs).…”
Section: Resultsmentioning
confidence: 99%
“…Pairwise SNP comparison showed that the isolates were identical to each other ( Figure 2 and Supplementary Figure 1), which supports transmission between these patients or acquisition from a common hospital source. In addition, 2 patients with community-onset LA-MRSA CC398 BSI, a 63-year-old man receiving outpatient dialysis (case E) and a 74-year-old male nursing home resident (case I), were previously reported to be part of 2 distinct healthcare outbreaks [ 14 ]. All 5 isolates from cases E, P, and Q were closely related to Danish pig isolates (range, 14–16 SNPs).…”
Section: Resultsmentioning
confidence: 99%
“…A recent prospective study of swine farm workers in Holland found that carriage of ST398 MRSA was not associated with elevated risk of infections, healthcare contact, or measures of reduced quality of life [ 60 ]. Somewhat surprisingly, the small numbers of fatal human cases of ST398 infection have occurred in people without known livestock contact, but who were generally medically compromised [ 61 ]. Even though there are a small number of fatal human cases of ST398 infections, it is important to better understand the interchange of S. aureus between humans and animals and the implications for the transfer of resistance elements.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, given that both lineages have a broad host spectra and recognized zoonotic potential it underlines the possible transmission risk to other endangered species and to zoo personnel. In addition, the potential for inter-human transmission of both of these MRSA lineages has been already demonstrated, 59,60 therefore contact with staff working in zoos could to be a risk factor to assess when investigating the epidemiology of MRSA in people without livestock contact.…”
Section: Discussionmentioning
confidence: 99%